Sasang Constitutional Medicine and Traditional Chinese Medicine: A Comparative Overview. (19th September 2011) - Yoo, Junghee; Lee, Euiju; Kim, Chungmi; Lee, Junhee; Lixing, Lao
Abstract : Sasang constitutional medicine (SCM) is a holistic typological constitution medicine which balances psychological, social, and physical aspects of an individual to achieve wellness and increase longevity. SCM has the qualities of preventative medicine, as it emphasizes daily health management based on constitutionally differentiated regimens and self-cultivation of the mind and body. This review's goal is to establish a fundamental understanding of SCM and to provide a foundation for further study. It compares the similarities and differences of philosophical origins, perspectives on the mind (heart), typological systems, pathology, and therapeutics between SCM and traditional Chinese medicine (TCM). TCM is based on the Taoist view of the universe and humanity. The health and longevity of an individual depends on a harmonious relationship with the universe. On the other hand, SCM is based on the Confucian view of the universe and humanity. SCM focuses on the influence of human affairs on the psyche, physiology, and pathology.